Nutrients dynamics and trophic status of lake Kenyir - Mohd Salleh, Ahmad Fathi; Rahman, Mohammad Mustafizur; Yunus, Kamaruzzaman; Mispan, Muhamad Radzali (2017)
Information about nutrients dynamics is very important for the lake’s productivity and ecosystem. Such information is lacking in the case of lake Kenyir, which is the largest man-made lake in Malaysia. A 12-month study (Jan-Dec 2017) was conducted to understand spatio-temporal nutrients dynamics and trophic status of the lake Kenyir. The study was conducted in three sampling zones (downstream, middle and upstream) in the Tekak river located northeast of lake Kenyir. Each sampling zone was subdivided into three sampling sites, which were considered as replications. The distance between any two sampling sites was approximately 500 m. A series of water quality parameters (temperature, dissolved oxygen, pH, conductivity, nitrate-nitrogen, nitrite-nitrogen and ammonia-nitrogen, phosphate-phosphorous and chlorophyll-a) and trophic status were determined monthly in each sampling site. Results indicate that all water quality parameters remained within expected ranges for aquatic animal particularly for fish. According to Malaysian National Water Quality Standards, most of the water quality parameters are in class I. All water quality parameters significantly (p<0.05) changed over time, showing peaks at different sampling days. All water quality parameters (except total suspended solid and turbidity) in all sampling zone were statistically similar (p>0.05). Both total suspended solid and turbidity decreased from upstream to downstream. Chlorophyll-a showed two low value loops: one from March to May and another from August to December. The highest chlorophyll-a was observed in June compared to other months. A significant negative correlation (r=-0.29, p<0.01) was observed between chlorophyll-a and temperature. TRIX index significantly changed over time. It indicates that water of lake Kenyir was oligotrophic (low productive) with low nutrients concentrations. The results of this study are very important for regular ecological monitoring and conservation of the lake. A proper management can improve the productivity of this lake.